The Ascent of Tokyo as an International Financial Center - Reed, Howard Curtis (Journal of International Business Studies, 1980)
This research traces, from 1900 to 1975, the rise of Tokyo to prominence as an international financial center in Asia by examining the evolution and development of seventeen Asian international financial centers. Cluster analysis is used to show the hierarchical structure of the international centers, over time. Stepwise multiple discriminant analysis is then used to verify the cluster analysis groupings, determine what factors caused the particular groupings, and rank the centers. The findings show clearly that Tokyo became Asia's preeminent “banking” center in 1960 and the preeminent “financial” center in 1965, but these results are at odds with the commonly held view that Singapore and Hong Kong are the region's top centers; in fact, Asia's second most prominent center is Osaka. The future implication and significance of Tokyo's (and Osaka's) financial leadership in Asia is discussed.